Observation of events with an energetic forward neutron in deep inelastic scattering at HERA - Derrick, M; Krakauer, D; Magill, S; Mikunas, D; Musgrave, B; Okrasinski, JR; Repond, J; Stanek, R; Talaga, R; Zhang, H; Mattingly, M; Bari, G; et al. (1996)
In deep inelastic neutral current scattering of positrons and protons at the center of mass energy of 300 GeV, we observe, with the ZEUS detector, events with a high energy neutron produced at very small scattering angles with respect to the proton direction. The events constitute a fixed fraction of the deep inelastic, neutral current event sample independent of Bjorken x and Q2 in the range 3 · 10-4 < xBJ < 6 · 10-3 and 10 < Q2 < 100 GeV2.